Workplace Spirituality and Job Satisfaction: Exploring Mediating Effect of Organization Citizenship Behaviour. Issue 3 (September 2019) - Garg, Naval; Punia, B. K.; Jain, Anuradha
This decade witnesses renewed interest in research studies on workplace spirituality (WSP). The present research investigates the relationship between WSP and job satisfaction (JS) with the help of two approaches. First, with the help of necessary condition analysis (NCA), it is explored that whether WSP is a necessary condition for the occurrence of JS. Second, the mediation effect of organizational citizenship behaviour (OCB) in association amid WSP and JS is examined using Baron and Kenny's (1986) technique of mediation analysis. A sample of 194 managers working in insurance companies is collected for the study. The study reports a positive correlation between all three variables of the study. Further, WSP does not come out as a necessary condition for JS. A partial mediation effect of OCB is reported. Practical implications and limitations are also discussed in the article.